2007
DOI: 10.1242/jeb.003749
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between food availability, glycerol and glycogen levels in low-temperature challenged rainbow smelt Osmerus mordax

Abstract: SUMMARY Rainbow smelt Osmerus modax accumulate glycerol in winter that serves as an antifreeze. Fish were held at 8°C, or subjected to a decrease in water temperature to –1°C over a 19 day period, and subsequently maintained at –1°C from 15 January to 11 May 2004. Starved fish did not survive the challenge of temperature decrease, with death ensuing above the typical freeze point for marine teleosts (–0.8°C). A decrease in temperature activates the glycerol accumulation mechanism at about 5°C wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 15 publications
2
47
0
Order By: Relevance
“…These patterns are also very similar to the one reported by Lewis et al (17), all of them closely fitting one on each other. The predictable decrease in glycerol levels observed in February supports the hypothesis that the decrease of glycerol levels from midFebruary is not triggered by temperature but by some other factor, such as photoperiod (7).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…These patterns are also very similar to the one reported by Lewis et al (17), all of them closely fitting one on each other. The predictable decrease in glycerol levels observed in February supports the hypothesis that the decrease of glycerol levels from midFebruary is not triggered by temperature but by some other factor, such as photoperiod (7).…”
Section: Discussionsupporting
confidence: 73%
“…An elevated GK activity at the end of the cycle might be related to the restoration of glycogen stores in liver suggested previously (7). Regulation of GK activity may be controlled by small increases in water temperature above the winter minima.…”
Section: Perspectives and Significancementioning
confidence: 61%
See 1 more Smart Citation
“…It is found that the variation in liver glycogen content was changing not in a fashion on addition of various fat content in the diet. Similar studies on the glycogen content estimated by many authors [11][12][13][14][15]. Digestive enzyme pattern of two stomachless filter feeders, silver carp, Hypophthalmichthys molitrix Val., and bighead carp, Aristichthys nobilis has been reported [41].…”
Section: Discussionsupporting
confidence: 78%
“…Email:ppsicar @ gmail.com, Fax : 91-22 26361573; ph: 91-22-26361446 like Johnston and Goldspink [11] in crucian carp; Driedzic and Short [12] in rainbow smelt; Diwan et al [13]; Peres and OlivaTeles [14] in European seabass and Bakthavatsalam and Reddy [15] in climbing perch. Similarly studies dealing with effect of feeding various lipids through diets on the muscle protein and intestinal protease in fish tissues have been reported by many authors [16][17][18][19].…”
Section: * Corresponding Authormentioning
confidence: 99%